Pengembangan Model Layanan Pendidikan Creative Art Play Therapy bagi Anak Berkebutuhan Khusus - Nasrah, Sayni; Siraj, Siraj; Dahrum, Dahrum (Jurnal Paedagogy, 2022)
This study aims to design a model of creative art play therapy education services to overcome various basic problems in providing friendly services for children with special needs (ABK) at Azura Sejati Inklusif PAUD Lhokseumawe. This study uses the Research and Development Borg and Gall method. The subjects in this study were teachers at the Azura Sejati Inklusif PAUD Lhokseumawe. The data used are qualitative and quantitative data, with data collection techniques through observation, interviews, documentation, questionnaires, and Focus Group Discussions (FGD). The data analysis technique used descriptive statistical analysis and inferential statistics. The results showed that the creative art play therapy educational service model was effectively used to provide friendly services for children with special needs (ABK) in dealing with social problems and self-control. All creative art play processes (1) creative visualization can stimulate children's understanding and thought processes; (2) storytelling activities can develop moral and spiritual; (3) drama can improve social relations, hand puppets and masks have been used to protect themselves; (4) art to develop creativity and aesthetic experience; (5) music to communicate; (6) dance and movement to develop physical motor skills.